2023
DOI: 10.7759/cureus.33976
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multifocal Intraocular Lens Implantation in Extreme Axial Myopia: A Case Report and Literature Review

Abstract: The prevalence of high myopia is rising globally. In addition to an increased risk of retinal detachment, high myopia is associated with earlier cataract formation. Patients with myopia are also often more motivated to become spectacle-independent after a lens procedure. However, the use of multifocal intraocular lens (MfIOL) remains controversial for patients with extreme myopia, which is classified as patients with an axial length >28 mm. Here, we present the case of a 64-year-old patient with visually signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…From pseudophakic monovision to bifocal IOLs, and then to rotational asymmetric IOLs, upgraded IOLs were constantly apply for cataract patients with high myopia to achieve vision with a range of distances [8,[20][21] , but the results were not satisfactory. In recent years, a few doctors started trying to implant trifocal IOLs into highly myopic eyes, even with AL of >30 mm or patients with nasal-inferior staphyloma [22][23][24] . The researches showed that trifocal IOLs can achieve better predicted vision for cataract patients with high myopia, however, there are still some problems in previous studies.…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringsmentioning
confidence: 99%
“…From pseudophakic monovision to bifocal IOLs, and then to rotational asymmetric IOLs, upgraded IOLs were constantly apply for cataract patients with high myopia to achieve vision with a range of distances [8,[20][21] , but the results were not satisfactory. In recent years, a few doctors started trying to implant trifocal IOLs into highly myopic eyes, even with AL of >30 mm or patients with nasal-inferior staphyloma [22][23][24] . The researches showed that trifocal IOLs can achieve better predicted vision for cataract patients with high myopia, however, there are still some problems in previous studies.…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringsmentioning
confidence: 99%